2011
DOI: 10.1055/s-0029-1245935
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Aberrant Right Subclavian Artery (ARSA) – a Potential New Soft Marker in the Genetic Scan?

Abstract: The presence of an ARSA is more common in fetuses with trisomy 21 and other chromosomal defects than in healthy fetuses. Although it can be considered as a weak marker, the second trimester diagnosis of an ARSA should prompt a detailed search for additional "soft markers" and structural defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 15 publications
1
51
2
1
Order By: Relevance
“…Several authors recommended karyotyping even if ARSA is the only positive marker [5,11], while it has been claimed that ARSA without another sonographic finding is not a powerful enough argument to recommend karyotyping [12]. In three previous series there was no case of trisomy 21 with isolated ARSA [4,6,12]. On the contrary, Chaoui et al [2] reported 5 cases of trisomy 21 having ARSA, and in 1 (20%) of them ARSA was the only positive sonographic marker.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors recommended karyotyping even if ARSA is the only positive marker [5,11], while it has been claimed that ARSA without another sonographic finding is not a powerful enough argument to recommend karyotyping [12]. In three previous series there was no case of trisomy 21 with isolated ARSA [4,6,12]. On the contrary, Chaoui et al [2] reported 5 cases of trisomy 21 having ARSA, and in 1 (20%) of them ARSA was the only positive sonographic marker.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether ARSA can be used as an isolated marker of Down syndrome, or only in combination with cardiac or extracardiac sonographic findings is yet to be established. Some of the previous studies showed the presence of trisomy 21 in cases with isolated ARSA [2,9,10,11], while in the other studies ARSA was associated with another sonographic finding in all cases with a chromosomal anomaly [4,6,12]. Moreover, the estimated likelihood ratio of isolated ARSA for Down syndrome was reported as 3.94 in a meta-analysis [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to highlight the relevance of the anatomy of the subclavian arteries, especially in cases of an aberrant right subclavian artery, where this vessel is absent in view IX. Interest in an aberrant right subclavian artery has increased, owing to its association with trisomy 21 and cardiac defects, 10,12,[35][36][37][38][39] although this association seems less marked when the condition is isolated. 16 Other authors have also reported on the possibility of observing the right subclavian artery under normal conditions in the second trimester.…”
Section: View Ix: Subclavian Arteriesmentioning
confidence: 99%
“…Além disso, sua existência está associada a cromossomopatias, nomeadamente trissomia do 21, e/ou malformações cardíacas 4 . Vários estudos de diagnóstico pré-natal recentes estimam que a incidência de ARSA varie entre 7,8-37,5% nos fetos com trissomia do 21 e 0,6-1,5% nos fetos cromossomicamente normais [5][6][7][8][9][10][11][12][13] . O diagnóstico pós-natal de ARSA em ecocardiografia de rotina não é fácil, dificultando o cálculo da sua incidência, quer na população normal, quer nos indivíduos com cromossomopatia e/ou malformações cardíacas 8 .…”
Section: Introductionunclassified